Direct Intermolecular Force Measurements between Functional Groups and Individual Metallic or Semiconducting Single‐Walled Carbon Nanotubes. Issue 4 (19th September 2013) - Thong, Ya Xuan; Poon, Yin Fun; Chen, Tzu‐Yin; Li, Lain‐Jong; Chan‐Park, Mary B.
<x xml:space="preserve">Abstract</x> Many electronic applications of single‐walled carbon nanotubes (SWNTs) require electronic homogeneity in order to maximally exploit their outstanding properties. Non‐covalent separation is attractive as it is scalable and results in minimal alteration of nanotube properties. However, fundamental understanding of the metallicity‐dependence of functional group interactions with nanotubes is still lacking; this lack is compounded by the absence of methods to directly measure these interactions. Herein, a novel technology platform based on a recently developed atomic force microscopy (AFM) mode is reported which directly quantifies the adhesion forces between a chosen functional group and individual nanotubes of known metallicity, permitting comparisons between different metallicity. These results unambiguously show that this technology platform is able to discriminate the subtle adhesion force differences of a chosen functional group with pure metallic as opposed to pure semiconducting nanotubes. This new method provides a route towards rapid advances in understanding of non‐covalent interactions of large libraries of compounds with nanotubes of varying metallicity and diameter; presenting a superior tool to assist the discovery of more effective metallicity‐based SWNT separation agents.